Born Too Soon: The global epidemiology of 15 million preterm births - Blencowe, Hannah; Cousens, Simon; Chou, Doris; Oestergaard, Mikkel; Say, Lale; Moller, Ann-Beth; Kinney, Mary; Lawn, Joy (Reproductive health, 2013)
This second paper in the Born Too Soon supplement presents a review of the epidemiology of preterm birth, and its burden globally, including priorities for action to improve the data. Worldwide an estimated 11.1% of all livebirths in 2010 were born preterm (14.9 million babies born before 37 weeks of gestation), with preterm birth rates increasing in most countries with reliable trend data. Direct complications of preterm birth account for one million deaths each year, and preterm birth is a risk factor in over 50% of all neonatal deaths. In addition, preterm birth can result in a range of long-term complications in survivors, with the frequency and severity of adverse outcomes rising with decreasing gestational age and decreasing quality of care. The economic costs of preterm birth are large in terms of immediate neonatal intensive care, ongoing long-term complex health needs, as well as lost economic productivity. Preterm birth is a syndrome with a variety of causes and underlying factors usually divided into spontaneous and provider-initiated preterm births. Consistent recording of all pregnancy outcomes, including stillbirths, and standard application of preterm definitions is important in all settings to advance both the understanding and the monitoring of trends. Context specific innovative solutions to prevent preterm birth and hence reduce preterm birth rates all around the world are urgently needed. Strengthened data systems are required to adequately track trends in preterm birth rates and program effectiveness. These efforts must be coupled with action now to implement improved antenatal, obstetric and newborn care to increase survival and reduce disability amongst those born too soon. Declaration This article is part of a supplement jointly funded by Save the Children's Saving Newborn Lives programme through a grant from The Bill & Melinda Gates Foundation and March of Dimes Foundation and published in collaboration with the Partnership for Maternal, Newborn and Child Health and the World Health Organization (WHO). The original article was published in PDF format in the WHO Report "Born Too Soon: the global action report on preterm birth" (ISBN 978 92 4 150343 30), which involved collaboration from more than 50 organizations. The article has been reformatted for journal publication and has undergone peer review according to Reproductive Health 's standard process for supplements and may feature some variations in content when compared to the original report. This co-publication makes the article available to the community in a full-text format.